Together or apart: Learning of translation-ambiguous words*. (October 2014) - DEGANI, TAMAR; TSENG, ALISON M.; TOKOWICZ, NATASHA
<x content-type="archive" xml:space="preserve">Abstract</x> In a multiple-session training study, native English speakers learned foreign Dutch vocabulary items that mapped to English either in a one-to-one way (translation-unambiguous) or in a one-to-many way (translation-ambiguous), such that two Dutch words corresponded to a single English translation. Critically, these two translation-ambiguous Dutch words were taught on consecutive trials in the same session, or were presented separately, such that each word was taught in a separate session. Translation-ambiguous words were produced and recognized substantially less accurately than translation-unambiguous words on tests administered one and three weeks after training. An ambiguity advantage emerged, however, in a free-recall test. Interestingly, teaching both translations together led to superior performance over teaching them in separate sessions, in which case the translation learned first enjoyed a considerable advantage over that learned second. These findings underscore the importance of order of acquisition in second-language vocabulary learning, and have practical implications for language instruction.